Influence of Friendship Circles on Variations in English Language Style Among University Students - Ali, Sahrin; Ente, Amelia Ramadhani R. Ente; Rahim, Marsela Hasan; Kaloh, Jesira Meisarah; Dako, Rahman Taufiqrianto; Katili, Adriyansyah Abu Katili (UIR Press, 2026)
This study investigates how friendship circles influence university students’ English language styles, focusing specifically on pronunciation adaptation and communication patterns. The research employed a descriptive qualitative design supported by quantitative data, involving 10 purposively selected students from an English Language Education Program in Indonesia. Data were collected using an online questionnaire consisting of multiple-choice and open-ended questions, then analyzed using three-step model: data reduction, data display, and conclusion drawing. The findings reveal four key patterns of language variation shaped by peer interaction: (1) pronunciation adaptation, (2) communication style, (3) peer influence, and (4) slang and informal lexicon. Students exhibited partial pronunciation accommodation, often adopting certain native-like features while maintaining local accents to balance group belonging and identity. Communication patterns were dominated by casual, slang-filled interactions, with academic discourse used primarily in formal contexts. Peer groups emerged as linguistic communities, subtly shaping pronunciation, lexical choice, and register through daily interactions. These findings contribute to sociolinguistic and psycholinguistic discussions on language variation, highlighting how peer social environments function as powerful spaces of linguistic adaptation and identity negotiation among EFL students. The study also emphasizes that language adaptation within peer groups is not merely linguistic, but also a reflection of emotional bonding and shared values. Understanding this process helps illustrate how English learning becomes a social practice shaped by identity, community, and belonging.